Hubungan Antara Sedentary Lifestyle dengan Status Gizi pada Peserta Didik Kelas VII SMPN 13 Surabaya - Zein Alijati Mustafa; Arifah Kaharina (MAN Insan Cendekia Jambi, 2026)
The study aimed to determine the relationship between sedentary lifestyle and nutritional status among seventh-grade students at SMPN 13 Surabaya. This study was a quantitative cross-sectional study with a correlational design. The population consisted of all 345 seventh-grade students, and a sample of 92 students was selected using random sampling. The instruments used were the Adolescent Sedentary Activity Questionnaire (ASAQ) to measure sedentary lifestyle and BMI/U measurement to determine nutritional status. Data analysis was performed using cross-tabulation and Spearman's rank correlation test with IBM SPSS Statistics 25 software. The results showed that most students were in the high sedentary lifestyle category (89 students, 96.7%) and had good nutritional status (67 students, 73%). There was no significant relationship between sedentary lifestyle and nutritional status among seventh-grade students at SMPN 13 Surabaya (p=0.0334; p>0.05). Although no relationship was found, increasing physical activity remains essential for optimal health.